On Double Clitics in Interrogatives in a Northern Italian Dialect - Nicoletta Penello (Nordlyd: Tromsø University Working Papers on Language & Linguistics, 2007)
Following recent studies (see for instance Poletto 2000) on the higher functional field, in this paper I aim to give a contribution to the cartography of the CP projection, by examining the behaviour of subject and object clitics in the Northern Italian dialect of Carmignano di Brenta, in comparison with the nearby dialect spoken in Padua. I will examine the characteristics and restrictions of two particular patterns found in main interrogatives in Carmignano, more specifically the co-occurrence of proclitic and enclitic subject and object clitics in yes-no and wh-interrogatives: I will label these structures “Two-Subject-Clitics” (= 2-Scl) and “Two-Object-Clitics” (= 2-Ocl), respectively. I will also support a structural analysis of 2-Scl and 2-Ocl. The analysis of microvariation and the comparison with Paduan will permit us to refine the generalisations formulated on the observations of the data of Carmignano and to establish implicational scales. Moreover, once we deal with very subtle variation which brings forth new data and phenomena, we can further enrich theoretical proposals that are already very accurate.